2016
DOI: 10.3329/bhj.v30i2.28812
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Surgery: Analysis of 102 Cases

Abstract: Abstract:Congenital heart diseases (CHDs) are a group of problems in the structure of the heart that is present at birth. Signs and symptoms depend on the specific type of problem. Symptoms can vary from none to life-threatening. CHD is prevalent throughout the world including Bangladesh. It is the leading cause of birth defect-related death. Most of the patients with CHDs need corrective surgery and life-long follow up with heart care. In this series, 102 cases of CHD patients were operated, 82 of them were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Mollah et al found that most often children are presented by 1 years of age. 10 Hussain et al found 44.99% CHD were diagnosed during neonatal period. 19 The diagnosis in 75.43% of cases was made under one year of age, in the research conducted in Hazara.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mollah et al found that most often children are presented by 1 years of age. 10 Hussain et al found 44.99% CHD were diagnosed during neonatal period. 19 The diagnosis in 75.43% of cases was made under one year of age, in the research conducted in Hazara.…”
Section: Discussionmentioning
confidence: 98%
“…9 According to recent update report of the American heart association, ASD, VSD, TOF, PDA, pulmonary stenosis, aortic stenosis, coarctation of aorta, and atrio VSD accounts for 85% of all CHDs. 10 Thus this study was conducted in a paediatric cardiology department of Bangladesh Shishu hospital and Institute which is a tertiary care hospital in Bangladesh with the aim to determine the current pattern of distribution of CHD in the population and age at which initial diagnosis of CHD was made.…”
Section: Introductionmentioning
confidence: 99%
“…Its symptoms depend on the specific type of anomaly and therefore symptoms may vary widely, ranging from none to those of life-threatening severity (2). CHD is also a major cause of infant mortality worldwide (3).…”
Section: Introductionmentioning
confidence: 99%